Performance evaluation of a diffusive hydrogel-based passive sampler for monitoring of polar organic compounds in wastewater - Fialová, Pavla; Grabic, Roman; Grabicová, Kateřina; Nováková, Petra; Švecová, Helena; Kaserzon, Sarit; Thompson, Kristie; Vrana, Branislav (The Science of the total environment, 2023)
An upscaled passive sampler variant (diffusive hydrogel-based passive sampler; HPS) based on diffusive gradients in thin films for polar organic compounds (o-DGT) with seven times higher surface area (22.7 cm2) than a typical o-DGT sampler (3.14 cm2) was tested in several field studies. HPS performance was tested in situ within a calibration study in the treated effluent of a municipal wastewater treatment plant and in a verification study in the raw municipal wastewater influent. HPS sampled integratively for up to 14 days in the effluent, and 8 days in the influent. Sampling rates (Rs) were derived for 44 pharmaceuticals and personal care products, 3 perfluoroalkyl substances, 2 anticorrosives, and 21 pesticides and metabolites, ranging from 6 to 132 mL d-1. Robustness and repeatability of HPS deteriorated after exposures longer than 14 days due to microbial and physical damage of the diffusive agarose layer. In situ Rs values for the HPS can be applied to estimate the aqueous concentration of the calibrated polar organic compounds in wastewater within an uncertainty factor of four. When accepting this level of accuracy, the HPS can be applied for monitoring trends of organic micropollutants in wastewater.
Keywords: Perfluoroalkyl substances; In situ calibration; Pharmaceuticals; Currently used pesticides; o-DGT; Sampling rate